Impact of decisions taken on the functioning of communication network Institutions in DRC (Democratic Republic of Congo) - SENGI, Symphorien BAMBISINGO (IJRDO - Journal of Business Management, 2019)
The relation between management of organizations and enterprises and Impact of decisions taken within the communication Network constitutes a phenomenon which is still unclear. Until now, we don’t know how to face the matter. Far from the end of the issue, the present article [assignment] proposes on original view which represents an added value allowing the best understanding of this phenomenon. In spite of existing of several theories, looking forwards to eliciting [clarifying] this relation, the universal theory [managerial approach] will be taken in account. In applying exclusively qualitative and quantitative methodological this research paper shows out the positive facts that will occur by applying certain practices of decisions taken on the functioning of communication network institutions in DRC.